CXCR4-overexpressed exosomes from cardiosphere-derived cells attenuate myocardial ischemia/reperfusion injury by transferring miRNA to macrophages and regulating macrophage polarization: CXCR4-overexpressed CDC-derived exosomes - Ma, Yanfeng; Su, Mingyu; Qian, Wei; Xuan, Yongli; Chen, Tao; Zhou, Ran; Jiang, Tingbo (Cellular and Molecular Biology, 2023)
Cardiosphere-derived cells (CDCs) are emerging as ideal candidates for managing cardiac inflammation, albeit with some limitations. Recent literatures have indicated that exosomes secreted by CDCs with C-X-C motif chemokine receptor 4 (CXCR4) overexpression can promote cardiac function after myocardial infarction and there have been some reports of miRNAs involved in ischemia/reperfusion (I/R) therapy. Therefore, we are interested in the role of CXCR4-overexpressed CDC-derived exosomes in delivering specific miRNA after myocardial I/R injury. In this research, we first constructed CDC-derived exosomes that overexpressed CXCR4 and miR-27a-5p, miR-182, or miR-101a. Then, we co-cultured the engineered exosomes with RAW264.7 cells and injected them intravenously into myocardial I/R model mice. In vitro, results showed that proinflammatory cytokines levels in the culture supernatant were decreased and the expression of M2 phenotypic markers were increased. Administration of engineered exosomes improved cardiac function, reduced infarct size, alleviated macrophage infiltration, and regulated M2 macrophage polarization after myocardial I/R, suggesting their implications in cardiac injury repair.